Characteristic of Sediment Verticaly on Abrasion Beach in Rupat Strait Riau Province - Rochman, Fatchur; Rifardi, Rifardi; Ghalib, Musrifin (Jurnal Perikanan dan Kelautan, 2018)
The research has been investigated on November 2017 which located on Rupat Strait, Riau Province. The purpose of this research to conducted character alteration vertically on sediment. 2 sampling point was tooken using 120 cm pipe. Were the result show that sediment dominated by mud. Based on shepard triangle there is 3 kind of sediment which is sandy mud, muddy sand and mud. The mean size (Mz) result for station I and II around 2,97-6,13∅ and contains 4 fraction sediment : medium silt which mean size (Mz) 5,03-6,00, corse silt which mean size (Mz) 4,07-5,00∅, fine sand which mean size (Mz) 2,97∅, and fine silt which mean size (Mz) 6,03-6,13∅.